2022
DOI: 10.1051/0004-6361/202141415
|View full text |Cite
|
Sign up to set email alerts
|

The eROSITA view of the Abell 3391/95 field: The Northern Clump

Abstract: Context. Galaxy clusters grow through mergers and accretion of substructures along large-scale filaments. Many of the missing baryons in the local Universe may reside in such filaments as the Warm-Hot Intergalactic Medium (WHIM). Aims. SRG/eROSITA Performance Verification (PV) observations revealed the binary cluster Abell 3391/3395 and the Northern Clump (the MCXC J0621.7-5242 galaxy cluster) are aligning along a cosmic filament in soft X-rays, similarly to what has been seen in simulations before. We aim to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
3
5
0
Order By: Relevance
“…Dolag et al 2006). The configuration of group B roughly ∼3 Gyr ago and the whole picture shown since then, that is, between z ∼ 0.25 and z ∼ 0.16, is consistent with the properties of the observed Northern Clump in the eROSITA A3391/95 field (Veronica et al 2022), which is located at a similar projected distance of about three virial radii from the A3391 cluster (Reiprich et al 2021;Veronica et al 2022).…”
Section: Additional Structures In the Local Environmentsupporting
confidence: 77%
See 3 more Smart Citations
“…Dolag et al 2006). The configuration of group B roughly ∼3 Gyr ago and the whole picture shown since then, that is, between z ∼ 0.25 and z ∼ 0.16, is consistent with the properties of the observed Northern Clump in the eROSITA A3391/95 field (Veronica et al 2022), which is located at a similar projected distance of about three virial radii from the A3391 cluster (Reiprich et al 2021;Veronica et al 2022).…”
Section: Additional Structures In the Local Environmentsupporting
confidence: 77%
“…While entering the outer atmosphere of GC1 (z 0.16), it undergoes gas stripping, as marked by the decrease in bound gas mass by a factor ∼3. The configuration corresponding to 3 Gyr ago (z ∼ 0.25) shares several similarities with the case of the real Northern Clump relative to A3391, supporting the picture of its actual infalling motion towards the A3391/95 system (see Veronica et al 2022). The eROSITA superior soft response and large FoV has allowed the first direct detection of the faint X-ray emission from the diffuse gas in the bridge and filaments connected to A3391/95, drawing a consistent picture of the LSS that compares well to theoretical predictions.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, if an emission bridge does connect the two clusters, the eRASS image will provide its observation. More generally, given the early eROSITA results on cluster outskirts and infall regions (e.g., Reiprich et al 2021;Ghirardini et al 2021;Churazov et al 2021;Veronica et al 2022;Whelan et al 2021;Sanders et al 2022), and given the close correspondence to similar structures observed in cosmological hydrodynamical simulations (e.g., Biffi et al 2022), we may expect that bridges and clumpy filaments will be discovered in several more nearby systems in the future in the eRASS. These systems can then be studied in detail after the eight surveys are completed using the SRG/eROSITA scanning mode, with which areas of tens of square degrees can be scanned efficiently, homogeneously, and deeply.…”
Section: Discussionmentioning
confidence: 72%